EFL Learners’ Self-Efficacy and Learning Strategies in The Learning English - Ailla Mahani Fadya Haya S; Desi Rusmawaty; Yuni Utami Asih (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2023)
The purposes of this research were (1) to investigate the self-efficacy level and learning strategies of EFL Learners in the learning English at English Education Department of Mulawarman University of Samarinda; (2) to investigate the kind of learning strategies of EFL Learners in the learning English at English Education Department of Mulawarman University of Samarinda; (3) to investigate the correlation between self-efficacy level and learning strategies of EFL Learners in the learning English at English Education Department of Mulawarman University of Samarinda. This research utilized correlation research. The researcher took 100 students in sixth semester at English Education Department of Mulawarman University of Samarinda as the sample in this research. The researcher used a questionnaire as an instrument in this research. The result of this research showed that most of students or 73 (73%) of students had High criteria of self efficacy in learning English speaking. While 8 (8%) of the students had Highest criteria. Therefore, 18 (18%) of the students had Average criteria. Then, one of the students (1%) had lowest criteria. In addition, no one had low criteria. It means that most of the students had High level of self efficacy in learning English speaking. According to result of spearman correlation, the correlation coefficient obtained was 0.167, which means that correlation between learning strategies and self-efficacy have a week correlation, it can be concluded that the relationship between learning strategies and self-efficacy were extremely weak. This also evidenced by the significant value of spearman correlation obtained 0.098 was higher than 0.05 which means that there is no significant correlation between learning strategies and self-efficacy of EFL Learners in English at English Education Department of Mulawarman University of Samarinda.